Analysis of Customer Experience, Ease of Use and E-WOM User Satisfaction of the Wondr Application - Intana, Tasya; Parhusip, Austin Alexander; Adam, Aisyah Azhar (International Journal of Islamic Business and Management Review, 2025)
The objective of this research is to investigate the individual and combined effects of customer experience, ease of use, and e-WOM on user satisfaction with the Wondr application at BNI USU Branch. A causal associative approach this function is used to check the relationship between these variables through quantitative methods. The population of this study includes users of the Wondr application, with a sample of 100 respondents selected using the convenience sampling method. The findings suggest that ease of use and e-WOM significantly and positively influence user satisfaction, both individually and together. The results showed that customer experience had no significant effect on user satisfaction (significance value 0.262 > 0.05), while ease of use and e-WOM had a significant effect. Ease of use (significance value 0.009 < 0.05) and e-WOM (significance value 0.007 < 0.05) are proven to have a positive and significant influence on user satisfaction. Overall, the variables of customer experience, ease of use, and e-WOM together have a significant effect on user satisfaction (significance value 0.000 < 0.05). The determination test result show that the adjusted R Square value 0.573 means that 57,3% of the factors that affect user satisfaction are explained by customer experience, ease of use, and e-WOM, while the remaining 42.7% can be caused by other factors not analyzed in this study.